PENGELOLAAN KEGIATAN EKSTRAKULIKULER PASCA PANDEMI DI SD MUHAMMADIYAH 7 BANDUNG - Syamsiah, Dian Nur; Hasanah, Enung (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Extracurriculars are school programs that aim to develop students' potential, interests and talents. In addition, as a material to improve student achievement. In its implementation, good and regular management is needed so that these extracurricular activities can run well. This study aims to determine the management of extracurricular activities at SD Muhammadiyah 7 after the Covid-19 pandemic. By using qualitative methods and descriptive research types. From the results of the research, it was found that SD Muhammadiyah 7 in its management underwent a change in the management system which was initially managed by an independent institution under the Muhammadiyah Regional Leadership Foundation in Bandung City, now it is managed by the school's own management. In its stages 1) Make SOP / standard extracurricular management rules. (2) Create an easier registration system for parents. (3) Make a one semester lesson plan for each type of extracurricular.